Identification of Peptoniphilus vaginalis-Like Bacteria, Peptoniphilus septimus sp. nov., From Blood Cultures in a Cervical Cancer Patient Receiving Chemotherapy: Case and Implications - Wang, Huacheng; Yang, Jin-Lei; Chen, Chunmei; Zheng, Ying; Chen, Mingming; Qi, Junhua; Tang, Shihuan; Zhan, Xiao-Yong (Frontiers in Cellular and Infection Microbiology, 2022)
A 39-year-old woman with a 3-year human papillomavirus (HPV) 18 infection history was admitted to the hospital for a 16-day history of vaginal bleeding after sex. She was diagnosed with cervical cancer based on the results of the electronic colposcopy, cervical cytology, microscopy, and magnetic resonance imaging (MRI). Then, she received chemotherapy, with paclitaxel 200 mg (day 1), cisplatin 75 mg (day 2), and bevacizumab 700 mg (day 3) twice with an interval of 27 days. During the examination for the diagnosis and treatment, many invasive operations, including removal of intrauterine device, colposcopy, and ureteral dilatation, were done. After that, the patient was discharged and entered the emergency department about 2.5 months later with a loss of consciousness probably caused by septic shock. The patient finally died of multiple organ failure and bacterial infection, although she has received antimicrobial therapy. The blood cultures showed a monobacterial infection with an anaerobic Gram-positive bacterial strain, designated as SAHP1. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI–TOF MS) indicated that the patient was infected with Peptoniphilus asaccharolyticus, while molecular analysis and genome-based taxonomy confirmed the infection with a novel Peptoniphilus species that has a close genetic relationship with Peptoniphilus vaginalis and proposed provisionally as Peptoniphilus septimus sp. nov., which may also act as a commensal of the human vagina. Genomic features of SAHP1 have been fully described, and comparative genomic analysis reveals the known prokaryote relative of Peptoniphilus septimus sp. nov. in the genus Peptoniphilus. The invasive operations on the genital tract during the diagnosis and treatment of the patient and the tumor tissue damage and bleeding may have a certain role in the bloodstream infection. This study casts a new light on the Peptoniphilus bacteria and prompts clinicians to include anaerobic blood cultures as part of their blood culture procedures, especially on patients with genital tract tumors. Furthermore, due to the incomplete database and unsatisfying resolution of the MALDI–TOF MS for Peptoniphilus species identification, molecular identification, especially whole-genome sequencing, is required for those initially identified as bacteria belonging to Peptoniphilus in the clinical laboratory.